COMPARISON BETWEEN THE PROVISION OF FEED FERMENTATION RICE STRAW AND LAWN KING OF CONSUMPTION, BODY WEIGHT GAIN AND FEED CONVERSION ON THIN TAIL CATTLE SHEEP - Busono, Hadi Suryo (Jurnal Sains Peternakan, 2015)
The purpose of this Research was to conducted at the Sheep Ranch Owned Enterprises Mr Zaenal Village Bandar Kedungmulyo Jombang on October 1, 2013 to 17 November 2013. Material used is a local sheep with four tails the average weight of 15 kg were given in the form of feed consists of two treatments. The method is a comparative study that comparation 2 treatment in feeding the sheep. The first treatment, in the form of concentrates fed lamb and king grass for 28 days, then replaced with concentrate feed and hay ferment for 28 days. The second treatment, sheep fed a concentrate and hay fermented for 28 days, then replaced with king grass feed concentrates and feed intake for 28 days and body weight gain. Data analysis techniques with RAL test. The results showed rapids feeding fermented rice and king grass no influence on the body weight and there influence on consumption and feed conversion in thin tail sheep. Thus, fermentation can replace grass hay king as sheep feedKeywords : straw fermentation, lamb, king grass, analytical descriptionÂ